Moving across Differences How Students Engage LGBTQ+ Themes in a High School Literature Class - Blackburn, Mollie V. (State University of New York Press, 2022)
Grounded in ethnography and teacher research, Moving across Differences examines how an LGBTQ+-themed literature course enabled high school students to negotiate their differences and engage in ethical encounters. Drawing on the work of queer theorists, Mollie V. Blackburn conceptualizes these encounters as forms of movement across differences of not only gender and sexuality but also identity and ideology more broadly. As we follow Blackburn's thoughtful rendering of students' sometimes fraught exchanges, we are encouraged to follow their lead and move when confronted with differences. We might move closer to those like us, so we can be in community to recover and heal. But we might also move closer to others, so we can discover and learn. The book argues, though, that we must move ethically and, moreover, that literature and the work of reading, writing, and talking can foster this movement. Modeling care in both teaching and research, Moving across Differences contributes to the study and practice of English Language Arts curriculum and pedagogy, qualitative methods, and queer theory.This book is freely available in an open access edition thanks to TOME (Toward an Open Monograph Ecosystem)-a collaboration of the Association of American Universities, the Association of University Presses, and the Association of Research Libraries-and the generous support of The Ohio State University Libraries. Learn more at the TOME website, available at: https://www.openmonographs.org/. It can also be found in the SUNY Open Access Repository at https://soar.suny.edu/handle/20.500.12648/7524